2006
DOI: 10.1615/jlongtermeffmedimplants.v16.i5.90
|View full text |Cite
|
Sign up to set email alerts
|

Acceptable Differences in Sensory and Motor Latencies Between the Median and Ulnar Nerves

Abstract: The median and ulnar nerves are often studied during the same electrodiagnostic examination. The sensory and motor latencies of these nerves have been compared to detect a common electrodiagnostic entity: median neuropathy at the wrist. However, this comparison could also be used to diagnose less common ulnar pathology. For this reason, it is important to establish normal values for comparing median and ulnar sensory and motor latencies. Previous research deriving these differences in latency has had some limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…These tests, in addition to the lumbrical-interossei study (not assessed in the present study), are important for evaluating patients with carpal tunnel syndrome. Our findings are consistent with the median-ulnar digit SNAP comparison study reported by Grossart et al 26 and the median-ulnar mixed palmar PL difference reported by Buschbacher. 27 Another study reported a slightly larger median-ulnar D4 PL difference (0.5 ms) than the values in our study.…”
supporting
confidence: 94%
“…These tests, in addition to the lumbrical-interossei study (not assessed in the present study), are important for evaluating patients with carpal tunnel syndrome. Our findings are consistent with the median-ulnar digit SNAP comparison study reported by Grossart et al 26 and the median-ulnar mixed palmar PL difference reported by Buschbacher. 27 Another study reported a slightly larger median-ulnar D4 PL difference (0.5 ms) than the values in our study.…”
supporting
confidence: 94%
“…This means that the ulnar motor latency should not be longer than the median motor latency. If it is, then ulnar nerve pathology across the wrist may be present . Median and ulnar sensory nerve latency comparisons, in contrast to the motor nerve comparisons, did not show a substantial age influence.…”
Section: Resultsmentioning
confidence: 90%
“…Median and ulnar sensory nerve latency comparisons, in contrast to the motor nerve comparisons, did not show a substantial age influence. For the entire group, the median‐to‐ulnar peak latency comparison had an upper (97th percentile) limit of 0.4 ms, whereas the ulnar‐to‐median upper limit comparison was similar at 0.5 ms (Table ) …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Less than 10% of patients with clinical CTS have normal NCV results. [26][27][28][29][30] In these cases, the treating physician should be sure that the most sensitive and specific NCV tests are done. If not, a request for these tests should be made.…”
Section: Nerve Conduction Velocitymentioning
confidence: 99%